Correlation Between PSA Density and Gleason Score In Prostate Cancer Patients (Bangladesh Journal of Urology, 2020)
Background: Prostate cancer is the most common form of malignancy and the second leading cause of cancer death among men. The histological grade is an independent determinant of disease prognosis and survival. The Gleason System (GS) grading is the most widely accepted classification. Several recent studies have searched for factors that could predict GS upgrading. High prostate specific antigen density (PSAD) has been shown to be predictors of risk progression in many studies, reflecting the possibility of undetected aggressive cancer.Objective: To detect the association between PSA density and Gleason score in prostate cancer patients.Methodology: This cross sectional study was carried out at the department of urology, Sir Salimullah Medical College Mitford hospital, Dhaka. Patients diagnosed as prostate cancer meeting the inclusion criteria admitted in the above mentioned place was the study population. Statistical analyses were carried out by using the Statistical Package for Social Sciences version 23.0 for Windows (SPSS Inc., Chicago, Illinois, USA). Student t-test was used for continuous variables. Pearson’s correlation coefficient was used to test the relationship between the groups. P values 3.0 ng/ml/ml. The difference was statistically significant (p